Comparison of the efficacy of three dental methods for estimating the age of persons aged 13 to 23 years - Suárez-Canlla, Carlos (2021)
Objective. To compare the efficacy of three dental methods (Demirjian, modified Gleiser-Hunt, and morphometric analysis) based on the root development of the lower third molars to determine age estimation on 13 to 23-years-old participants. Methods. The sample included 978 orthopantomographs of people with known chronological age and sex (484 men and 494 women). The root development of the molars was classified according to the indicated methods. The concordance of the sample was performed based on a second classification of 10% of the sample. The stages of root development - obtained with the aforementioned methods - and the chronological age were correlated to obtain: 1) the correlation and determination index 2) the regression formulas that predict age and 3) the difference between the real chronological age and the estimated dental age for each method. Results. The modified Gleiser-Hunt method obtained the lowest residual result of the difference between chronological and dental age, as well as the best correlation index with chronological age. The difference between chronological and dental age was 1.55, 1.68 and 2.11 for the modified Gleiser-Hunt, Demirjian and morphometric analysis methods respectively. Conclusions. The modified Gleiser-Hunt method was more effective in predicting the age of people and individuals aged 13 to 23-years-old.